Ultrasonographic gastric volume before unplanned surgery. (11th July 2017) - Dupont, G.; Gavory, J.; Lambert, P.; Tsekouras, N.; Barbe, N.; Presles, E.; Bouvet, L.; Molliex, S.
Summary: We aimed to measure gastric antral cross‐sectional area with ultrasound and estimate the gastric volume of 300 patients before unplanned surgery, fasted for at least six hours. Measurements were successfully recorded in 263 semi‐recumbent patients. The median (IQR [range]) area was 333 (241–472 [28–1803]) mm 2 and the mean (SD) estimated volume was 45.8 (34.0) ml. The area exceeded 410 mm 2 in 92/263 (35%) measurements. Body mass index and morphine administration were associated with larger gastric areas on multivariable linear regression analysis, with beta coefficient (95%CI) 0.02 (0.01–0.04), p = 0.01, 0.23 (0.01–0.46), p = 0.04, respectively. Fasting time was not associated with gastric area and therefore could not substitute for ultrasound measurements in this cohort.